Development and Validation for Extended Reality-Based MIS Simulator Using Cumulative Summation. Issue 5 (16th March 2022) - Qin, Zhibao; Wang, Yinjia; Du, Junzhen; Tai, Yonghang; Shi, Junsheng
ABSTRACT: Minimally invasive surgery (MIS) is gradually replacing traditional open surgery. Novices need a lot of practice in the surgical simulator to master surgical skills. Therefore, this paper developed an extended reality-based minimally invasive surgery (MIS-XR) simulator, which includes VR, AR and IVR simulators, and introduces the traditional Box simulator to compare these four simulators. Twenty-two subjects were divided into the expert group (6) and novice group (16) and were invited to participate in the experiment. Face, content, and construct validation methods were used to evaluate the tactile sense, visual sense, scene authenticity, and performance of the four simulators. The cumulative summation was used to further analyze the learning curve of 30 times training for the novice group, to verify the effectiveness of the four simulators and determine which simulator can improve the operator's surgical skills more quickly. The results of the face and content validation show that the Box simulator is the strongest among the four simulators in the tactile sense, IVR simulator is superior to the Box simulator and VR simulator in scene authenticity. The result of construction validation shows that the four simulators are not only useful in improving the surgical skills of novices but also retain the surgical skills after a period of rest. The MIS-XR simulator developed in this paper is effective and can be used as a training device of surgical skills for novices.